Price discovery in the Trinidad and Tobago fixed-rate government bond market : preliminary study - Campbell Gill, Michelle ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2006)
Presents a preliminary analysis of the price discovery process in the Trinidad & Tobago fixed-rate government bond market and the efficacy of the single-price auction system vis-à-vis price discovery.